(untitled) (Journal of Uzbekistan’s Development and Research, 2025)
This paper explores the application of the morphological method in cross-cultural analysis. Originally developed for structuring and solving complex problems, the morphological method proves to be highly effective in the field of comparative cultural studies. It enables the identification and comparison of structural elements within cultural systems—such as values, behavioral patterns, symbols, and rituals—and facilitates the analysis of their possible combinations and interactions. The study outlines the principles and stages of morphological analysis and demonstrates its practical use in comparing cultural artifacts, norms, and worldviews across various ethnic and national groups. Special attention is given to the method’s potential in interdisciplinary research, including sociology, anthropology, and intercultural communication. The conclusion emphasizes the value of the morphological approach as a tool for gaining a deeper understanding of cultural diversity and fostering sustainable models of intercultural dialogue.